Identifying symmetry in running gait using a single inertial sensor - Lee, J. B.; Sutter, K. J.; Askew, C. D.; Burkett, B. J. (Journal of Science and Medicine in Sport, 2010)
Running gait has been shown to alter due to changes in intensity. It was hypothesised that a sacral mounted single inertial sensor could identify the centre of mass (COM) vertical accelerations. This study aimed to validate this new technique against a criterion measure and to determine the influence of changes in running intensity on COM vertical acceleration and the symmetry of COM vertical acceleration between left and right steps. Ten athletes ran for 5 min at their self-selected pace, plus 1 km/h above and below this velocity. Validity of the single inertial sensor was determined by comparing COM vertical acceleration against that measured with a six-camera infrared system. Large correlation (r = 0.96), a small typical error of estimate (1.84), and mean bias (0.02) were found between the two systems. The greatest magnitude in COM vertical acceleration occurred at the slowest running pace and decreased as pace increased. Sixty percent of the athletes exhibited asymmetry during at least one running pace; 30% were asymmetrical across all three velocities. While significant changes in COM vertical acceleration occurred between the different running velocities, this did not always result in a change in symmetry. This study found that a single inertial sensor can be used as a valid means of measuring COM vertical acceleration. This technique can detect changes in the COM vertical acceleration that may change with running velocity. Gait symmetry (using COM vertical acceleration) during running was also quantified using the inertial sensor.